Everyone is a Teacher Method in Improving Arabic Learning Outcomes - Rotul Krisdayanti, Aprilia; aziz, Noor; Astina, Chairani (DAS Institute, 2025)
This study aimed to improve Arabic learning outcomes for Grade VIII students at MTsN 2 Wonosobo by applying the Everyone Is a Teacher Here method during the 2024/2025 academic year. Using a quantitative experimental design with 56 students divided equally into an experimental group and a control group, the study compared the effectiveness of this method against conventional teaching. Both groups took a pretest before instruction and a posttest afterward. The experimental class engaged in active learning by writing questions related to the material, which enhanced participation. Analysis of the data showed a moderate improvement in learning outcomes for the experimental group with an N-Gain score of 0.61, compared to 0.35 in the control group. Statistical testing confirmed a significant difference between the two groups, demonstrating that the Everyone Is a Teacher Here method effectively increased students’ Arabic learning outcomes more than traditional methods.